Cinema e cidadania comunicativa: sessões comentadas na ocupação Pandorga e na Sala Redenção: cinema universitário de Porto Alegre - Pires, Maytê Ramos (Universidade do Vale do Rio dos Sinos, 2017)
This research had as general goal to investigate and to understand the processes of debate in the commented sessions realized in Ocupação Pandorga and in Sala Redenção conceived into the perspective of the construction of a communicative cinematographic citizenship. The concepts that underpinned the investigation, essential for the realization of the dialogue with the empirical in the construction of the analysis, were: reception of cinema, spatialities, cinephilia, communicative citizenship thought for the scope of the cinematographic reception, mediatization, mediations, media appropriations and cineclubism. In the concretization of the research, a contextualization of aspects related to the constitution of the circuit of cinemas in Porto Alegre was carried out, particularizing those where debates take place, considering links with elements related to the wider cinematographic context, cineclubs, urban occupations and, specifically, Ocupação Pandorga and Sala Redenção scenario. The methodological dimension of the research was built on the promotion of dialogue between the theoretical and empirical fields, in a coming and going that led to constant changes in the research until it establishes its nucleus at the moment of the debates. The methodological procedures worked were of theoretical research, of contextualization and research of the research. The empirical research was conducted from observations of commented cinema sessions and occasional interviews, of different modalities. The results obtained in the investigation indicate that both spaces have potentialities in the construction of citizen actions in the field of cinema and suggestions are proposed in order that both Ocupação Pandorga and Sala Redenção can advance in the direction of commented sessions of citizen cinema, in terms of a communicative citizenship designed for the cinematographic field.
Keywords: Recepção; Cidadania comunicativa cinematográfica; Sessões comentadas de cinema; Ocupação Pandorga; Sala Redenção; Reception; Cinematographic communicative citizenship; Commented movie sessions; ACCNPQ::Ciências Sociais Aplicadas::Comunicação